2017
DOI: 10.1016/j.transproceed.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Newly Developed BETA-2 Scoring System for Pancreatic Islet Graft Function Assessment

Abstract: BETA-2 score was successfully validated externally and is a practical tool allowing for frequent and reliable assessments of islet graft function based on a single fasting blood sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Our results indicate that BETA-2 and TEF could safely be implemented in the assessment and management of glucose control in patients after TP-IAT. TEF outperformed other surrogate indices in the AUROC analysis unlike in our previous analysis in allogenic islet transplant recipients [21]. However, BETA-2 showed the strongest correlation with all the reference beta-cell function measures in the current study, and was found very efficient not only in auto-but also in allotransplantation.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Our results indicate that BETA-2 and TEF could safely be implemented in the assessment and management of glucose control in patients after TP-IAT. TEF outperformed other surrogate indices in the AUROC analysis unlike in our previous analysis in allogenic islet transplant recipients [21]. However, BETA-2 showed the strongest correlation with all the reference beta-cell function measures in the current study, and was found very efficient not only in auto-but also in allotransplantation.…”
Section: Discussioncontrasting
confidence: 76%
“…It is particularly important that all the cut‐offs for detection of the need for insulin support are similar to those in allogenic islet transplantation recipients: BETA‐2 score below 13 indicating insulin dependence, between 13 and 18 signifying glucose intolerance and score over 18 was correlated with insulin independence . Due to a limited number of MMTT measurements in our patients, we stratified patients only as “on insulin” and “off insulin” and found a cut‐off of 16.2, which is in the middle between 13 and 18 found in islet allograft patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BETA‐2 showed >88% specificity and sensitivity in detecting insulin independence with a cut‐off of 15, whereas a BETA‐2 cut‐off of 20 had >82% sensitivity and specificity in detecting glucose intolerance . Our subsequent external BETA‐2 validation presented very similar results . We also used BETA‐2 to measure islet graft function on day 75 and found that it can also predict insulin independence at 1 year posttransplantation (AUC = 0.942 [0.869‐1]) ( P = .001) .…”
Section: Discussionmentioning
confidence: 72%
“…Some studies have demonstrated that a positive C-peptide before pancreas transplantation was not associated with worse patient or graft survival [15]. In the field of islet transplantation, C-peptide is a component of the β-Score which is routinely used to estimate beta cell functionality [16][17][18].…”
Section: Introductionmentioning
confidence: 99%